Knowledge of HPV, its vaccines, and attitudes toward HPV vaccines among obstetrician-gynecologists, pediatricians and immunization services providers in Western China. Issue 1 (31st January 2022) - Ma, Jianqiao; Zhang, Xi; Wang, Wei; Zhang, Rong; Du, Mei; Shan, Li; Li, Yucong; Wang, Xiaohui; Liu, Yijun; Zhang, Wen; Li, Xiaoling; Qiao, Youlin; et al.
ABSTRACT: Background: In mainland China, HPV vaccines have been available to the public. However, only a few related studies among health care providers, as the key information providers, were reported although public concerns on HPV vaccines still exist. In this study, we aim to assess the knowledge of HPV, its vaccines, and attitudes toward HPV vaccines among the three most important groups of health care providers in Western China. Method: This was a cross-sectional questionnaire-based study. Health care providers including obstetrician-gynecologists (OB-GYNs), pediatricians, and immunization service providers in Western China were investigated regarding their knowledge of HPV and its vaccines and their attitudes toward HPV vaccines. Results: Of 1079 health care providers completing the survey, 1015 (94.1%) knew HPV infection is the primary cause of cervical cancer. However, lower knowledge levels of other HPV-related diseases were also found (43.2%). About three-quarters (74.1%) of practitioners interviewed would be willing to recommend HPV vaccination, which was found to be lower among the OB-GYNs (69.6%) and the pediatricians (73.2%). "Lack of relevant knowledge, " "concerns on safety and efficacy" and price were the three most important concerns surrounding HPV vaccination. Conclusion: The interviewed practitioners did not have adequate knowledge of HPV and its vaccines in depth. Education interventions are highly recommended to the health care providers, especially for OB-GYNs and pediatricians, to increase the coverage of HPV vaccination among the population. For the currently high price of vaccines, a future co-sharing mechanism between the government, the providers, and the individuals might be a solution.